1998
DOI: 10.1021/ac970954g
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic Electrogenerated Chemiluminescence of Luminol at Disposable Oxide-Covered Aluminum Electrodes

Abstract: Luminol exhibits strong electrogenerated chemiluminescence during cathodic pulse polarization of oxide-covered aluminum electrodes in aqueous solution. This electrogenerated chemiluminescence can be enhanced by the presence of dissolved oxygen or by the addition of other coreactants such as hydrogen peroxide, peroxydisulfate, or peroxydiphosphate ions. However, luminol detection is most sensitive in the presence of azide ions, which not only enhance the electrogenerated chemiluminescence intensity but also dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 32 publications
(117 reference statements)
1
42
0
1
Order By: Relevance
“…Many common photoluminescent and chemiluminescent luminophores have been detected this way, examples including luminol and its derivatives [10,11], Ru(bpy) 3 2+ [12,13], fluorescein and eosin [14], SYBR (R) Green I [15], coumarine dyes [16], Rhodamine B [17] and terbium chelates [18,19]. The most sensitive HECL luminophores so far are terbium labels, which can be detected down to femtomolar concentration [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Many common photoluminescent and chemiluminescent luminophores have been detected this way, examples including luminol and its derivatives [10,11], Ru(bpy) 3 2+ [12,13], fluorescein and eosin [14], SYBR (R) Green I [15], coumarine dyes [16], Rhodamine B [17] and terbium chelates [18,19]. The most sensitive HECL luminophores so far are terbium labels, which can be detected down to femtomolar concentration [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [22][23][24][25][26], we have demonstrated that many kinds of luminophores can be excited by cathodic pulse-polarization at conductor/insulator/electrolyte (C/I/E) tunnel junction electrodes e.g. oxide-coated aluminum, silicon and magnesium electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, cathodic reductions may be produced simultaneously by heterogeneously transferred electrons from the bottom of the conduction band of the insulating film, via the surface states of the insulating film and by presolvated hot and hydrated electrons [25]. Meanwhile, strongly oxidizing species such as sulfate and hydroxyl radicals can be cathodically generated from purposely-added coreactants or form dissolved oxygen [22,23,25,33,34]. In addition, F + -centers existing in oxide film of C/I/E electrodes may act as oxidants [2,23,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is being widely used as a useful tool in a chemical analysis. Up to now, a continuous flow injection, [4][5][6][7][8][9][10][11][12] liquid chromatography [13][14][15][16][17] and capillary electrophoresis (CE) [18][19][20][21] have been mainly connected with the optical system. A very good selectivity and a very low detection limit could be accomplished with these kinds of connections.…”
Section: Introductionmentioning
confidence: 99%